2007
DOI: 10.2166/wst.2007.271
|View full text |Cite
|
Sign up to set email alerts
|

Toward an operational dynamic model for tertiary nitrification by submerged biofiltration

Abstract: This work deals with the methodology put in place to fit and validate the parameters of a biofiltration model (BAF) in tertiary nitrification treatment and dynamic conditions. For an average loading rate of 0.65 kg NH4-N/m(3) media/d, different time loading rates are applied inside a filtration-backwash run using a semi-industrial pilot. Comparisons between predicted and observed values on the NH4-N, NO3-N and TSS in treated water and the total head loss deltaP are carried out firstly using default values of B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…These models, however, are only relevant if simulation results truly represent behavior and performance of the process. Practical experience in nitrifying/denitrifying treatment plants over the last 10 years at Cemagref (France) has shown that even for the simplest IWA-type model (ASM1), the original default parameter values needed to be reconsidered to match predictions with measurements (Boursier et al, 2004;Choubert et al, 2005Choubert et al, , 2006Choubert et al, , 2008Lessard et al, 2007;Marquot et al, 2006;Stricker et al, 2003;Vigne et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…These models, however, are only relevant if simulation results truly represent behavior and performance of the process. Practical experience in nitrifying/denitrifying treatment plants over the last 10 years at Cemagref (France) has shown that even for the simplest IWA-type model (ASM1), the original default parameter values needed to be reconsidered to match predictions with measurements (Boursier et al, 2004;Choubert et al, 2005Choubert et al, , 2006Choubert et al, , 2008Lessard et al, 2007;Marquot et al, 2006;Stricker et al, 2003;Vigne et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…An existing sensitivity analysis (Vigne et al, 2007) which has been completed with some additional tests on parameters has enabled to identify the most sensitive parameters and to set up a calibration protocol. The model has been calibrated and validated for both dry and wet weather, in two different plant configurations.…”
Section: Resultsmentioning
confidence: 99%
“…Environment Research, Volume 80, Number 10-Copyright © 2008 Water Environment Federation1085A sensitivity analysis was carried out and the hierarchy of biofiltration model parameters was classified into strong and low influence on the effluent concentrations of a submerged biofiltration nitrification process(Vigne et al, 2007). Simulation results showed that filtration module and the mean density of biofilm had strong influence on effluent total suspended solids (TSS) and the total head loss in the reactor, while effluent NH affected by the specific autotrophic growth rate, the maximum biofilm thickness and the reduction coefficient of diffusivity in the biofilm.…”
mentioning
confidence: 99%